Contratos tributários - Macedo, Erick (2020)
This work analyzes the possibility of using tax agreements. To do so, it initially analyzes the compatibility of such instruments with the constitutional principles, especially legal certainty, equality, efficiency, and legitimate expectations. In investigating the theme, this work evaluates the meaning and scope of the principle of legality, especially in regard to its limits, that the experience of its application has demonstrated, in achieving the values that it seeks to protect. In that regard, it is discussed the problem related to the construction of the meaning of the norm in the process of positivizing the law, particularly concerning the possibility of a consensual convention delimiting the scope and meaning of a legal norm. This study is also dedicated to addressing one of the most recurring objections to the use of tax agreements, which is the issue of non-disposability of the public interest. After overcoming those aspects, this work is dedicated to examining the legal nature of the obligations established by such agreements and concludes with the verification of their adoption’s requirements and, finally, with its types